New particle formation observed from a rain shadow region of the Western Ghats, India. Issue 7 (13th September 2020) - Varghese, Mercy; Leena, Parakkatt Parambil; Murugavel, Palani; Bankar, Shivdas; Todekar, Kiran; Chowdhuri, Subharthi; Safai, Pramod D.; Malap, Neelam; Konwar, Mahen; Dixit, Shivsai; Rao, Yeddu Jaya; Prabha, Thara V.
Abstract: This study reports on new particle formation (NPF) and characteristic features observed from a rural site falling in the rainshadow of the Western Ghats in peninsular India. A total of 35 NPF events observed during August 2018 - January 2019 are classified and analyzed here. The apparent formation rates ranged from 0.2 to 10.0 cm –3 s –1, while the growth rates of nucleation mode particles ranged from 1.2 to 13.8 nm h –1 . The frequency of occurrence was least during August (core monsoon) and highest during post-monsoon. The local winds were calm and southeasterly to easterly (from the urban centre) supplying the essential precursor gases during October and November, leading to a frequent occurrence of nucleation events. Observations suggest that an increased condensation sink could limit the NPF while promoting Aitken mode growth. The newly formed particles accounted for about 10–80% of the total aerosol concentration. These newly formed particles were able to act as cloud condensation nuclei after growing to approximately 50 nm with an average activation fraction of 0.4.